ENHANCING PROFESSIONAL TRAINING OF MUSIC TEACHERS THROUGH HISTORICAL MUSIC TRADITIONS - Nabijonov Ravshanbek Obidjon o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the use of historical music traditions to enhance the professional training of future music teachers. It highlights the importance of integrating historical, cultural, and artistic knowledge into pedagogical practice. The study discusses how engaging with historical musical works develops students’ technical skills, creative thinking, cultural awareness, and ethical understanding. Interactive and innovative approaches, including performance, analysis, and multimedia-supported activities, are emphasized as effective methods to strengthen professional competencies and prepare future educators for modern music teaching environments.